2011
DOI: 10.1182/blood-2011-05-352039
|View full text |Cite
|
Sign up to set email alerts
|

Molecular predictors of response to decitabine in advanced chronic myelomonocytic leukemia: a phase 2 trial

Abstract: IntroductionChronic myelomonocytic leukemia (CMML), which is the most frequent myelodysplastic/myeloproliferative disorder, 1 is characterized by the accumulation of monocytes and a variable proportion of immature dysplastic granulocytes in the PB and the BM. 2 Clonal cytogenetic abnormalities are detected in ϳ 40%, 3 and a copyneutral uniparental disomy in leukemic cells of ϳ 50% of the patients. 4 Mutations in ASXL1, TET2, and RUNX1 genes are detected in 25% to 50% of patients, RAS and CBL gene mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
163
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(172 citation statements)
references
References 46 publications
(70 reference statements)
8
163
1
Order By: Relevance
“…Indeed, both agents exert potent antileukemic effects in MDS and CMML. 42,43 Therefore, it is tempting to speculate that part of their antileukemic effect might also involve an induction of autophagy and myeloid differentiation. Nevertheless, the data presented herein deciphers the signaling pathways involved in CSF1-mediated induction of autophagy and monocyte differentiation, as well as paves a new research avenue for future therapeutic interventions through PRKAA reactivation in the context of CMML.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both agents exert potent antileukemic effects in MDS and CMML. 42,43 Therefore, it is tempting to speculate that part of their antileukemic effect might also involve an induction of autophagy and myeloid differentiation. Nevertheless, the data presented herein deciphers the signaling pathways involved in CSF1-mediated induction of autophagy and monocyte differentiation, as well as paves a new research avenue for future therapeutic interventions through PRKAA reactivation in the context of CMML.…”
Section: Discussionmentioning
confidence: 99%
“…Limited prospective data is available: AZA is licensed in Europe in CMML-2 patients with WBC <12 G/L, on the basis of the MDS AZA-001 trial where only few CMML patients were randomized [27]. A phase II study of DAC in high risk population of MP-CMML provided interesting results [71] prompting an ongoing randomized phase III trial addressing the role of DAC as upfront treatment of MP-CMML in the presence of adverse prognostic features (NCT02214407). As in other myeloid neoplasms, response to HMA remains difficult to predict in CMML with clinical variables or with gene mutations.…”
Section: Treatmentmentioning
confidence: 99%
“…The hypomethylating agents (HMA) azacitidine (AZA) and decitabine (DAC) seem active in CMML, though they have mostly been explored retrospectively [69,70], reporting overall response rates in the 40-70% range. In retrospective studies controlling for biases, there does seem to be a significant difference between DAC and AZA in this population (Duchmann et al, manuscript in preparation), even though several authors have suggested that DAC could be beneficial in proliferative CMML [70,71], possibly because standard regimens of DAC are slightly more myelotoxic than AZA regimens. HMA also seem active in patients with extra-medullary disease [71].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Most important, a recently concluded phase II trial in which 39 CMML patients were treated with decitabine suggested that lower CJUN and CMYB gene expression levels were independently associated with an improved overall outcome and survival. 43 However, the value of somatic gene mutations in the prognosis of CMML has not been validated and no scoring system including such molecular aberrations has been developed. …”
mentioning
confidence: 99%